History of the Association of Chinese Geneticists in America (ACGA) - Chen, PhD, FACMG, Andrew TL.; Yang, PhD, Huanming (North American Journal of Medicine and Science, 2013)
The Association of Chinese Geneticists in America (ACGA) is a non-profit (501C) organization formed by a group of American geneticists of Chinese ethnicity but its membership is open to individuals of all races and ethnicity. Incorporated in the State of Georgia in 1987, ACGA is supported by membership fees and donations. The Association facilitates the interaction between the American genetics community and their colleagues in mainland China, Taiwan, Hong Kong and Singapore. [N A J Med Sci. 2013;6(4):171-172.]